2021
DOI: 10.1155/2021/6469883
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based Diet and Iron Deficiency Anemia in Sundanese Adolescent Girls at Islamic Boarding Schools in Indonesia

Abstract: Background. Adolescent girls are at risk for iron deficiency anemia (IDA) due to the higher demand of iron for growth and the loss of blood during menstruation. Consumption of foods containing iron that have higher bioavailability can reduce the risk of IDA although diets that are largely plant-based, like those consumed by many Sundanese people, may not contain sufficient bioavailable iron. Here, we investigated the correlation between plant-based diets and IDA in adolescent Sundanese girls who were students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
1
13
0
5
Order By: Relevance
“…45 , 46 In the study reported by Rahfiludin, IDA was associated with less animal-based foods characterized by iron with higher bioavailability. 47 This finding can also explain why anemia in this study is more common in adolescents than in adults. One factor that causes anemia is an inadequate nutritional intake.…”
Section: Discussionmentioning
confidence: 60%
“…45 , 46 In the study reported by Rahfiludin, IDA was associated with less animal-based foods characterized by iron with higher bioavailability. 47 This finding can also explain why anemia in this study is more common in adolescents than in adults. One factor that causes anemia is an inadequate nutritional intake.…”
Section: Discussionmentioning
confidence: 60%
“…The majority of publications in other years highlighted the micro levels focus, such as iron pro les as screening 13) , meal patterning for treating Anemia. 4,[14][15][16][17] ) Anemia related obstetric outcome, 18) and correlation with malaria, 19) and also iron-folic acid supplementation anemia, 20) the traditional source of iron supplementation, 21,22) personal adherence to iron supplementation, [23][24][25] role of educational media, or health education. 26) Here, the publication attention lacked Meso-level publication involving the role of organization and community in the successful implementation of iron supplementation program.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional status R 0.05 P-value 0.55 N the incidence of anemia in the vegetarian and nonvegetarian groups. 40 Another study of adolescent girls in Jatinangor, using the Chi-square test, also found no significant difference between the distribution of nutritional status and the incidence of anemia. 35 A study using the BMI indicator also found no significant relationship between BMI and the prevalence of anemia in adolescents.…”
Section: Hemoglobin Levelmentioning
confidence: 96%